Enantioselective Synthesis of (–)-Stemoamide - Mi, Xianwei; Wang, Yan; Zhu, Lili; Wang, Renxiao; Hong, Ran (Synthesis, 2012)
An enantioselective synthesis of (–)-stemoamide is presented. Noyori’s ruthenium complex catalyzed asymmetric transfer hydrogenation of an alkynone delivered the (S)-C8 stereogenic center in 97.7% ee. An iron(III) chloride promoted and bioinspired N-iminium ion cyclization afforded a 3:1 ratio of two diastereomers in favor of the cis-isomer. The diastereomeric ratio was enriched to 50:1 by a silver-catalyzed cycloisomerization. The subsequent dynamic ruthenium-catalyzed CO-insertion reaction secured an enantioselective total synthesis of (–)-stemoamide in 18% overall yield with high optical purity.
Keywords: carbonylation; biomimetic synthesis; asymmetric transfer hydrogenation; iminium ion cyclization; stemoamide